Addressing Health Disparities Across the Cancer Continuum—a Los Angeles Approach to Achieving Equity - Finster, Laurel J.; Shirazipour, Celina H.; Escobedo, Loraine A.; Cockburn, Myles; Surani, Zul; Haile, Robert W. (Frontiers in Oncology, 2022)
Introduction: Different models have been developed to address inequities across the cancer care continuum. However, there remains a scarcity of best practices on understanding and responding to the burden of cancer in a defined catchment area. As such, the National Cancer Institute (NCI) recently provided a framework to maximize the impact on cancer burden, including a greater focus on community outreach and engagement. In this paper, we describe how Cedars Sinai Cancer (CSC), a health system that serves one of the most diverse counties in the US, implemented the framework to define its catchment area, characterize its population, identify high risk priority groups, and make decisions to address health disparities. Methods: We provide a review of the methods used to assess socio-ecological levels of influence. Data were reviewed from numerous national, statewide, and county sources and supplemented by locally administered questionnaires, heat maps, and community profile summaries to gain more localized snapshots of cancer disparities in Los Angeles County. Lastly, feedback was solicited from external peer groups, community stakeholders, and key decision-makers, and the proposed catchment area was aligned with the State’s Cancer Plan and the NCI Catchment Area and Community Outreach and Engagement Mandate. Results: The selected CSC catchment area meets NCI criteria and has potential to demonstrate impact both at the population level and within specialty populations. As a result, strategies are being developed to organize community outreach and engagement, as well as research across basic, clinical, and population sciences to guide cancer control and prevention efforts. Discussion: To maintain a high level of cultural inclusion and sensitivity, multiple layers of data are needed to understand localized pictures of cancer disparities and underlying causes. Community engagement remains essential to implementing policy, best practice, and translational science for broader impact. Impact: The clinical and translation work conducted at any cancer center requires an understanding of the determinants of health that contribute to the differences in cancer incidence and mortality among different groups. The NCI-aligned approach that we highlight is critical to support the design of future cancer control strategies that address and possibly reduce local health inequities.